The Oysterville sewing circle - Wiggs, Susan (New York : William Morrow, 2019)
At the break of dawn, Caroline Shelby rolls into Oysterville, Washington, a tiny hamlet at the edge of the raging Pacific. She's come home. Home to a place she thought she'd left forever, home of her heart and memories, but not her future. Ten years ago, Caroline launched a career in the glamorous fashion world of Manhattan. But her success in New York imploded on a wave of scandal and tragedy, forcing her to flee to the only safe place she knows. And in the backseat of Caroline's car are two children who were orphaned in a single chilling moment - five-year-old Addie and six-year-old Flick. She's now their legal guardian - a role she's not sure she's ready for. But the Oysterville she left behind has changed. Her siblings have their own complicated lives and her aging parents are hoping to pass on their thriving seafood restaurant to the next generation. And there's Will Jensen, a decorated Navy SEAL who's also returned home after being wounded overseas. Will and Caroline were forever friends as children, with the promise of something more...until he fell in love with Sierra, Caroline's best friend and the most beautiful girl in town. With her modeling jobs drying up, Sierra, too, is on the cusp of reinventing herself. Caroline returns to her favorite place: the sewing shop owned by Mrs. Lindy Bloom, the woman who inspired her and taught her to sew. There she discovers that even in an idyllic beach town, there are women living with the deepest of secrets. Thus begins the Oysterville Sewing Circle - where women can join forces to support each other through the troubles they keep hidden. Yet just as Caroline regains her creativity and fighting spirit, and the children begin to heal from their loss, an unexpected challenge tests her courage and her heart. This time, though, Caroline is not going to run away. She's going to stand and fight for everything - and everyone - she loves.
Keywords: Sewing -- Fiction; Life change events -- Fiction; Small cities -- Fiction; Washington (State) -- Fiction